Investigation of a selectable multi-passband microwave photonic filter based on cascaded optical comb filters - Wang, F.; Peng, M. M. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
A multi-passband microwave photonic filter (MPF) with selectable passband frequency, spanning 0–20 GHz frequency range, is proposed, and experimentally demonstrated, in which passband frequency can be flexibly selected within a maximum passband number to four. The scheme is based on the generation of tunable optical comb lines using a broadband optical source sliced by cascaded optical comb filters, achieved by connecting an in-line birefringence fiber filter and a reconfigurable Lyot filter in series, such that various filter tap spacing and spectral combinations are obtained for the configuration of the MPF. The proposed MPF can operate with four different passband states, namely, single-, dual-, triple-, and quadruple-passband, only by adjusting polarization states of the cascaded optical comb filters. All these passbands are with a 3-dB bandwidth varying from 200 to 460 MHz and more than 20-dB sidelobe suppression.
Optica Applicata, Vol. 51, 2021, nr 3, s. 457-467
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; microwave photonic filter; multi-passband filter; microwave signal processing